The role of anti-NHba antibody in bactericidal activity elicited by the meningococcal serogroup B vaccine, MenB-4C. Issue 33 (24th July 2017) - Partridge, Elizabeth; Lujan, Eduardo; Giuntini, Serena; Vu, David M.; Granoff, Dan M.
Highlights: MenB-4C (Bexsero®) is a multicomponent serogroup B meningococcal vaccine. The bactericidal role of antibody to one of the four antigens, Neisserial Heparin binding antigen (NHba), is incompletely understood. In 9 immunized adults, anti-NHba antibody contributed to SBA against some strains, particularly in concert with anti-FHbp antibody. One high NHba-expressing strain with an amino acid sequence identical to the vaccine was resistant. Predicting anti-NHba strain coverage is challenging based on antigen expression and reactivity. Abstract: Background: MenB-4C (Bexsero®) is a multicomponent serogroup B meningococcal vaccine. For vaccine licensure, efficacy was inferred from serum bactericidal antibody (SBA) against three antigen-specific indicator strains. The bactericidal role of antibody to the fourth vaccine antigen, Neisserial Heparin binding antigen (NHba), is incompletely understood. Methods: We identified nine adults immunized with two or three doses of MenB-4C who had sufficient volumes of sera and >3-fold increases in SBA titer against a strain with high NHba expression, which was mismatched with the other three MenB-4C antigens that elicit SBA. Using 1 month-post-immunization sera we measured the effect of depletion of anti-NHba and/or anti-Factor H binding protein (FHbp) antibodies on SBA. Results: Against three strains matched with the vaccine only for NHba, depletion of anti-NHba decreased SBA titers by an average of 43–79% compared to mock-adsorbed sera (P < 0.05). Despite expression of sub-family A FHbp (mismatched with the sub-family B vaccine antigen), depletion of anti-FHbp antibodies also decreased SBA by 45–64% (P < 0.05). Depletion of both antibodies decreased SBA by 84–100%. Against a strain with sub-family B FHbp and expression of NHba with 100% identity to the vaccine antigen, depletion of anti-NHba decreased SBA by an average of 26%, compared to mock-adsorbed sera (P < 0.0001), and depletion of anti-FHbp antibody decreased SBA by 92% (P < 0.0001). Conclusions: Anti-NHba antibody can contribute to SBA elicited by MenB-4C, particularly in concert with anti-FHbp antibody. However, some high NHba-expressing strains are resistant, even with an exact match between the amino acid sequence of the vaccine and strain antigens.